Low Carbon Virtual Lab (LCVL) on electricity to empower sustainability literacy of junior high school students - Salsabila Kholifahtun Nisa'; Muhammad Nur Hudha; Nurma Yunita Indriyanti; Riezky Maya Probosari; Lina Mahardiani; Kadek Dwi Hendratma Gunawan (Universitas PGRI Kanjuruhan Malang, 2025)
Electricity is a conceptual and complicated physics subject, hence technological integration is required to help understanding. Using the ADDIE development research approach, this study will investigate how the design, practicality, and characteristics of Low Carbon Virtual Lab (LCVL) media might empower students' sustainability literacy. The LCVL was built using low carbon education values and sustainability literacy indicators to test student abilities through quizzes and discussion topics. The feasibility of LCVL was rated as very good. Material experts scored 96.59%, media experts scored 86.98%, and language experts scored 95.60% (very feasible). The teacher and student response test to LCVL also yielded an overall average, with student responses of 91% and instructor responses of 82.41%. LCVL possesses the following characteristics: (1) an interactive digital simulation media, (2) packed in the form of a website link, (3) user-friendly, (4) utilized to empower students' sustainability literacy, and (5) the concept of electrical material supplied is combined with low carbon education. Thus, LCVL is appropriate for use in the learning process to improve students' sustainability literacy.